PENERAPAN MODEL PEMBELAJARAN KOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 44 DURI TIMUR KECAMATAN MANDAU KABUPATEN BENGKALIS - Gusmiance Gusmiance; Hendri Marhadi; Lazim Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on observations by the author in the academic year 2015/2016, the issue of lack of student learning outcomes is still a learning center teacher and often use the lecture method. Students are still less active and less passion, less attention in learning when the teacher explains, quickly get bored and talking with your seatmate. Students are less able to associate lessons learned with lessons to be learned. And things like that happen it causes the student's knowledge does not develop, the skills are not trained and students are not accustomed to solve its problems alone. IPS learning test results found to identify the problem as follows: Low levels of student ability, tetidakmampuan students complete assignments, students are less able to appear in front of the class present the results of the group work and the lack of instructional media as a supporter in the delivery of material. The subjects of this study are all fourth grade students who totaled 25 people and consists of 16 men and 9 women. In addition, researchers use the type of classroom action research conducted in two cycles during 4 meetings. Each cycle is carried out through four stages, namely planning, action, observation, and reflection. The data collection technique is carried out through tests, observations, and documentation. Activities of teachers and students using the Learning Koopertaif Type Numbered Heads Together (NHT) from the first cycle to the second cycle increased. So the use of Cooperative Learning Model in accordance denagan NHT expected. The results of students in grades Pre PTK obtained average is 67.2, while the first cycle with the average value is 71.4. For the second cycle occurred Improvement, the average value of 78.4. Improved student learning outcomes in basic score of 52%, UAS in the first cycle increased to 72% and the value of UAS in the second cycle to 92%.Key words: NHT, learning outcomes IPS